2006
DOI: 10.1111/j.1532-5415.2006.00770.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cataract Surgery on Falls and Mobility in Independently Living Older Adults

Abstract: Cataract surgery had no association with the occurrence of falls or mobility or balance problems in independently living older adults with a cataract.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 30 publications
1
44
1
Order By: Relevance
“…Neither visual acuity or stereopsis were independently associated with falls risk despite the fact that participants in this study had much poorer visual acuity and stereopsis than cataract patients in studies from developed countries. 10,28 It should be noted however, that this may be due to the small number of falls recorded in this study. Visual acuity is quite heavily relied on for measuring visual disability caused by cataract and prioritizing patients for surgery.…”
Section: Discussionmentioning
confidence: 65%
“…Neither visual acuity or stereopsis were independently associated with falls risk despite the fact that participants in this study had much poorer visual acuity and stereopsis than cataract patients in studies from developed countries. 10,28 It should be noted however, that this may be due to the small number of falls recorded in this study. Visual acuity is quite heavily relied on for measuring visual disability caused by cataract and prioritizing patients for surgery.…”
Section: Discussionmentioning
confidence: 65%
“…Limitations of the study by Brannan et al include lack of a control group of patients who did not have cataract surgery and a small sample size of 84 total patients. McGwin et al 14 reported that cataract surgery was not associated with decreased odds of falls. They compared patients with cataract who received and did not receive surgery.…”
Section: ͻ001mentioning
confidence: 99%
“…However, the difference in the number of falls between first- and second-eye surgery was not statistically significant. The participants of this study had considerably poorer presurgery vision than participants of the studies described earlier, which were conducted in developed countries 11,13,44. This may have contributed to the significant reduction in falls found among this Vietnamese cohort after surgery.…”
Section: Discussionmentioning
confidence: 70%
“…However, the study was not able to control for possible confounders, including visual measurements, and only examined more severe falls. In contrast, a prospective study found that cataract surgery had no impact on falls for an independently living older population 44. However, participants who had one- and both-eye cataract surgery were combined for the analysis and the sample size was small (n=122).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation